Effects of wheat source and particle size in pelleted diets on finishing pig growth performance, caloric efficiency, and carcass characteristics - De Jong, Jon A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Paulk, Chad B.; Woodworth, Jason C.; Jones, Cassandra K.; Stark, Charles R.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 576 pigs (PIC 327 × 1050; initially 96 lb BW) from 2 consecutive finishing groups were used to determine the effects of wheat source and particle size of pelleted diets on finishing pig growth performance, caloric efficiency, and carcass characteristics. Pigs were allotted randomly to pens upon entry into the finisher. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 6 dietary treatments with 12 replications per treatment and 8 pigs per pen in two groups of finisher pigs. The experimental diets all had the same wheat-soybean meal formulation, with the 6 treatments formed by including the wheat from 1 of 2 sources (hard red winter vs. soft white winter) that were processed to 1 of 3 mean particle sizes (200, 400, or 600 μ). All diets were fed in pelleted form. Overall, feeding hard red winter wheat improved (P < 0.05) ADG, ADFI, and caloric efficiency on both an ME and NE basis compared with soft white winter wheat. There was a tendency (P < 0.07) for a quadratic particle size × wheat source interaction for ADG, ADFI, and both DM and GE digestibility because the lowest ADG, ADFI, and both DM and GE digestibility values were for 400-μ hard red winter wheat, and the highest were for 400-μ soft white winter wheat. No significant (P > 0.10) main effects were detected of particle size, or of particle size within wheat source. Finally, dietary treatments did not affect carcass characteristics. In conclusion, decreasing wheat particle size from 600 to 200 μ in pelleted diets had no effect on growth performance. Feeding hard red winter wheat improved ADG and ADFI compared with feeding soft white winter wheat.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Finishing pig; Grinding; Pelleting; Wheat